Genome-wide analysis of the Drosophila immune response by using oligonucleotide microarrays. - De Gregorio, E.; Spellman, P.T.; Rubin, G.M.; Lemaitre, B. (Proceedings of the National Academy of Sciences of the United States of America, 2001)
To identify new Drosophila genes involved in the immune response, we monitored the gene expression profile of adult flies in response to microbial infection by using high-density oligonucleotide microarrays encompassing nearly the full Drosophila genome. Of 13,197 genes tested, we have characterized 230 induced and 170 repressed by microbial infection, most of which had not previously been associated with the immune response. Many of these genes can be assigned to specific aspects of the immune response, including recognition, phagocytosis, coagulation, melanization, activation of NF-kappaB transcription factors, synthesis of antimicrobial peptides, production of reactive oxygen species, and regulation of iron metabolism. Additionally, we found a large number of genes with unknown function that may be involved in control and execution of the immune response. Determining the function of these genes represents an important challenge for improving our knowledge of innate immunity. Complete results may be found at http://www.fruitfly.org/expression/immunity/.